(untitled) (Quaestiones Disputatae: temas en debate, 2021)
The theme of “Societies in Transition and Peacebuilding” is suggestive from the perspective of justice, peace and reconciliation, bearing in mind that the communities that suffer violence, discrimination, marginalisation and injustice at first hand are the black, Afro-Colombian, Raizal and Palenquero communities of Colombia, El Salvador, Guatemala and Peru, among other Latin American peoples. This article presents a study of the concomitance of the indigenous community with the black community, with numerous possibilities for the historian, theologian and sociologist of the 21st century, based on the guiding question: what is the importance and meaning of a culture of peace and reconciliation for a society that is moving from war to peace?